Decoupling African Traditional Religion and Culture from the Family Life of Africans: Calculated Steps in Disguise - BOAKYE, EBENEZER (International Journal of Multidisciplinary: Applied Business and Education Research, 2021)
Even though African Traditional Religion and Cultural family life seem to have been detached from the indigenous Africans, with many reasons accounting for such a detach, the attempts made by the new wave of Christianity is paramount, under the cloak of salvation and better life. The paper focuses on the steps taken by Pentecostal-Charismatics in Africa to decouple African Traditional Religion and Culture from the family life of Africans in a disguised manner. The paper begins with the retrospection of African Traditional Religion as the religion with belief of the forefathers concerning the existence of the Supreme Being, divinities, Spirit beings, Ancestors, and mysterious powers, good and evil and the afterlife. It then walks readers through the encounter between Christianity and ATR and come out that Christianity from its earliest history has maintained a negative attitude toward ATR. The paper again explores that the traditional understanding of the African family system is portrayed in the common believe system and the functions of the family components. Again, the paper further unravels decoupling measures such as reaching the masses for audience, demonization of African the world of the spirit, demonization of African elders, pastors assuming the traditional position of elders of African families are the factors that are being taken to ensure the taking away of African traditional religious and family life from Africans. The paper again discusses the adverse effects of these decoupling factors on Africans. The paper concludes that Traditional African family patterns are slowly but progressively being altered as a result of the process of the decoupling strategies